SCOPE OF AYURVEDA IN THE MANAGEMENT OF KUSHTHA (SKIN DISEASES) - Anjali Bhati; Chhaju Ram Yadav; Rashmi Gurao (International Research Journal of Ayurveda & Yoga, 2024)
Background: Skin disorders are multi-faceted and may have their origin in allergy, autoimmunity, and hereditary. Ayurveda describes skin disorders under the umbrella of Kushtha, a disease characterized by the derangement of the skin. When we take into account the prevalence of different diseases, over 20% of all people seeking medical attention each year are suffering from skin disorders globally. Kushtha is categorized as Maha Kushtha and Kshudra Kushtha by all Acharyas depending on the severity of the symptoms and its prognosis. Many different etiological factors and disease management strategies are described in the Ayurvedic system of medicine. Aim: To assess the scope of Ayurveda in the management of skin diseases. Material & Methods: Different classical Ayurvedic texts, websites, journals and research articles were referred in the above context. Discussion & Conclusion: Kushtha arises from the vitiation of Tridosha and Twak, Rakta, Mamsa and Lasika. Thus the management for Kushtha is based on the involvement of Dosha and Dushya. Though some treatment modalities are condition-specific, the fundamental principle of treatment is consistent with all forms of Kushtha. Acharya have emphasized the significance of Shodhana (detoxification) therapy to eliminate the morbid Dosha from the body, and Raktamokshana to expel Dushita Rakta which is the key Dushya in the pathology of Kushtha. The Shamana (palliative) therapy comprises both internal and external medications viz. Rasa Aushadhi, Churna, Kwath, Asav, Arishta, Guggulu, Ghrita, and Malhara, Tail, Lepa. Dietary management, Dincharya, Ritucharya, Rasayana therapy, and Sadvritta are given immense importance in Ayurveda to preserve good health and prevention of diseases. This wholesome viewpoint of detoxification, palliative care and lifestyle modification needs to be analyzed to develop guidelines for the management of skin diseases based on Ayurveda principles.